Tinjauan Komparatif Aplikasi Finite Element Method (FEM) Untuk Pemodelan Dan Analisis Perilaku Struktur Kompleks - Putra, Adli Shahzada; Ardhana, Arya (Journal of Infrastructure and Construction Technology, 2024)
This literature review presents a comparative analysis of various applications of the Finite Element Method (FEM) in the modeling and analysis of civil engineering structures, with a specific focus on cold-formed steel (CFS) connections and reinforced concrete columns. The primary aim of this research is to evaluate the precision and reliability of computational simulations in replicating complex structural behaviors under diverse loading conditions. The review methodology was conducted through a systematic selection of studies published between 2015 and 2025 that examine the effectiveness of FEM in comparison to analytical and experimental approaches. Aggregate results indicate that FEM exhibits a deviation of 25–29% from experimental outcomes in modeling Haunched Gusset Plate (HGP) connections within CFS structures, while effectively predicting bolt hole failure modes. In reinforced concrete columns, modeling using the Concrete Damage Plasticity (CDP) approach demonstrates an increase in axial capacity by 115–121% due to variations in stirrup configurations. Overall, this review confirms that FEM is an accurate and efficient predictive tool for analyzing the nonlinear behavior of structures and plays a vital role in structural optimization and enhancing the design reliability of modern engineering.